Pertanggungjawaban Produsen atas Keracunan MBG yang Ditinjau dari Undang-Undang Perlindungan Konsumen - Arlando; Ferdy Febrian (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The Free Nutritious Meal Program (MBG) represents a state policy designed to fulfill children’s right to adequate nutrition, yet its large-scale implementation poses significant food safety risks, particularly the occurrence of food poisoning incidents. The reliance on catering service providers places students in the position of vulnerable consumers who may be exposed to unsafe food products. This article examines the legal responsibility of producers for food poisoning cases within the MBG framework under Law Number 8 of 1999 on Consumer Protection, employing normative legal research through statutory and conceptual analysis. The findings indicate that catering producers may be held liable under the principle of strict liability as stipulated in Article 19 of the Consumer Protection Law, without requiring consumers to prove fault. Furthermore, civil liability based on unlawful acts under Articles 1365, 1366, and 1367 of the Civil Code provides a legal avenue for victims to seek compensation, either individually or through class action mechanisms. Despite these legal instruments, Presidential Regulation Number 83 of 2024 does not explicitly regulate liability mechanisms or sanctions for food providers, resulting in a regulatory gap that weakens consumer protection. Strengthening legal norms and supervisory mechanisms is therefore essential to ensure legal certainty and effective protection of children’s fundamental rights as beneficiaries of the Free Nutritious Meal Program.